Clinical and radiographical evaluation of a bioresorbable collagen membrane of fish origin in the treatment of periodontal intrabony defects: A preliminary study - B B Santosh Kumar; D R Aruna; Vinayak S Gowda; Sushama R Galagali; R Prashanthy; H Navaneetha (Wolters Kluwer Medknow Publications, 2013)
Background: Recently, there has been interest in non-mammalian collagen sources such as fish collagen in periodontal regeneration. In the present study, collagen barrier membrane of fish origin was assessed in the treatment of periodontal intrabony defects. Materials and Methods: Ten systemically healthy chronic periodontitis patients having a paired osseous defect in the mandibular posterior teeth were selected and randomly assigned to receive a collagen membrane (test) or open flap debridement (control) in a split mouth design. Clinical parameters such as Plaque index, Gingival bleeding index, Probing pocket depth, Relative attachment level, and Recession were recorded at baseline, 3, 6, and at 9 months, while radiographic evaluation was done to assess alveolar crestal bone level and percentage of defect fill at 6 and 9 months using autoCAD 2007 software. Student's t test (two-tailed, dependent) was used to find the significance of study parameters on continuous scale. Significance was set at 5% level of significance. Wilcoxon signed rank test was used to find the significance of percentage change of defect fill. Results: The comparison between the two groups did not show any statistically significant differences in the parameters assessed (P > 0.05) but, within each group, clinical parameters showed statistically significant differences from baseline to 9 months (P < 0.05). Conclusion: Within the limits of the study, it can be inferred that no significant differences were found either by using collagen membrane of fish origin or open flap debridement in the treatment of periodontal intrabony defects.